"Sex Seems Less Important When You Are Worried About a Deadly Virus." A Content Analysis of Reported Reasons for Changes in Sexual Behavior and Satisfaction During the COVID-19 Pandemic. Issue 1 (2nd January 2023) - Gleason, Neil; Conroy, Katherine; Taylor, Sophia; Smith, Lauren; Gasser, Melissa; Jennings, Todd; Lyng, Tayler; Coleman, Eli; Banik, Swagata
Abstract: The purpose of this study is to assess how the COVID-19 pandemic impacted various sexual behaviors and levels of sexual and relationship satisfaction by performing a content analysis of participants' (N = 1051 American adults) responses to open-ended survey questions. Results revealed a variety of impacts that increased, decreased, or otherwise qualitatively changed sexual behavior and satisfaction. Major themes included emotions and mental health, changes in routines, social distancing and fears related to COVID-19, and changes in romantic relationships. These findings are contextualized within the emerging quantitative research on COVID-19 and sexuality, and areas for future research based on these findings are discussed.